The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2333393620938686
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Good Nursing Practice for Medical Assistance in Dying in Canada: An Interpretive Descriptive Study

Abstract: Nurses play a central role in Medical Assistance in Dying (MAiD) in Canada. However, we know little about nurses’ experiences with this new end-of-life option. The purpose of this study was to explore how nurses construct good nursing practice in the context of MAiD. This was a qualitative interview study using Interpretive Description. Fifty-nine nurses participated in semi-structured telephone interviews. Data were analyzed inductively. The findings illustrated the ways in which nurses constructed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Participants also suggested that there was a component of the act that should never feel normal and they continued to feel the emotional impact, similar to what Flemish nurses reported many years after the legalization of euthanasia in Belgium [38]. These findings of calibration stand in contrast to our earlier interviews with nurses, conducted shortly after the legalization of MAID, in which participants described an unprepared healthcare system that left them with few practice supports to do the morally complex work that was required with this new legal responsibility [19,25,27].…”
Section: Cultural Calibrationsupporting
confidence: 65%
See 1 more Smart Citation
“…Participants also suggested that there was a component of the act that should never feel normal and they continued to feel the emotional impact, similar to what Flemish nurses reported many years after the legalization of euthanasia in Belgium [38]. These findings of calibration stand in contrast to our earlier interviews with nurses, conducted shortly after the legalization of MAID, in which participants described an unprepared healthcare system that left them with few practice supports to do the morally complex work that was required with this new legal responsibility [19,25,27].…”
Section: Cultural Calibrationsupporting
confidence: 65%
“…Accessibility to MAID was influenced by the sometime contentious relationship between those care providers involved in MAID and those in palliative care [19,22,23]. There was a need to support healthcare providers involved in MAID in light of the emotional impact [20,24,25] and a need to provide healthcare providers with the knowledge and skills to assist with, or to assess and provide, MAID, particularly in light of vague eligibility criteria [20,26,27]. There was also a need to manage the relational challenges that arose between those who saw MAID as an acceptable moral option and those who did not [19-21, 25, 26].…”
Section: Request Signed By One Independent Witnessmentioning
confidence: 99%
“…The purpose of this paper is to report on findings related to nurses' moral experiences in the context of MAiD from a qualitative interview study. This paper complements two other papers from the same set of interviews with 59 nurses in which we reported nurses' views on best practices and their experiences with health system issues (Pesut, Thorne, Schiller, Greig, & Roussel, 2020; Pesut et al., 2020).…”
Section: Introductionsupporting
confidence: 54%
“…Due to the Canadian sociocultural context, the government adopted a new concept for defining euthanasia: "medical aid in dying (MAiD)" to reflect specific values of Canadian culture. [13] The terminology most used internationally is "euthanasia", which refers to "an active and intentional act consisting in bringing death, following the request of a person experiencing unbearable physical or psychological suffering related to incurable and irreversible endof-life medical conditions " [14] while the concept of "medical assistance in dying" is defined as: "medical assistance that it is practised in a context of health care and is administered by a health professional [...] which puts its expertise at the service of the relief of suffering [Free translation]". [15] According to the C-14 Bill, to be eligible for MAiD in Canada, a person must meet the following criteria: (a) be eligible for government-funded health services in Canada; (b) be at least 18 years of age, i.e.…”
Section: Maid In Canada: Implementation Of the Role Of Npsmentioning
confidence: 99%